Exercise, manual therapy, and education with or without high-intensity deep-water running for nonspecific chronic low back pain: a pragmatic randomized controlled trial - Cuesta-Vargas, Antonio Ignacio; García-Romero, Jerónimo Carmelo; Arroyo-Morales, Manuel; Diego-Acosta, Angel Mario; Daly, Daniel J (American journal of physical medicine & rehabilitation, 2011)
The aim of this study on persons with nonspecific chronic low back pain was to evaluate the effect of a multimodal physical therapy program with or without the addition of deep-water running on pain, physical disability, and general health. A randomized controlled trial involving 46 subjects with nonspecific chronic low back pain were treated three times a week for 15 wks. Each group received 60 mins of multimodal physical therapy program (an individualized exercise program; manual therapy; and back care, pain education, and information on an active lifestyle), whereas one group performed additional 20-min sessions of deep-water running at an individual workload of the aerobic threshold. Both interventions resulted in significant improvements in pain, disability, and physical health. The mean change in pain, disability, and physical health state were -36.1 ± 25.1 mm on the visual analog scale, -3.0 ± 4.8 points for the Roland Morris Questionnaire, and 10.6 ± 12.9 points for the Short Form-12 for the physical therapy plus deep-water running group and -34.1 ± 26.0 mm on the visual analog scale, -1.6 ± 1.5 points for the Roland Morris Questionnaire, and 8.9 ± 13.0 points for the Short Form-12 for the physical therapy alone group. Pain, disability, health status, muscle strength and endurance, and lumbar range of motion significantly improved in both groups. The addition of a deep-water running program at an individual workload of the aerobic threshold to the multimodal physical therapy program produced a significant improvement in pain in patients with nonspecific chronic low back pain, but this was not significantly different when compared with multimodal physical therapy program alone. Disability, health status, muscle strength and endurance, and lumbar range of motion significantly improved to a similar level in both intervention groups.